EFFECTIVENESS OF SEMAGLUTIDE IN OBESITY TREATMENT AND THE ROLE OF LIFESTYLE INTERVENTIONS - Filip Bracichowicz,; Igor Winogrodzki,; Patryk Kowalczyk,; Hanna Paszkiewicz,; Kamil Nowak,; Aleksandra Gęsińska,; Alicja Stryczek-Schlusche,; Bartłomiej Trzciński,; Oliwia Gugała,; Aleksandra Magdalena Furczyńska, (International Journal of Innovative Technologies in Social Science, 2025)
Background: Obesity is a global epidemic, affecting ~13% of adults and driving type 2 diabetes, cardiovascular disease, and other comorbidities (World Health Organization, 2021). In Europe and the U.S., prevalence reaches 30–40%, with >20% in Poland (Gajewska & Harton, 2023). Lifestyle interventions alone often fail to ensure durable results, creating demand for adjunctive pharmacotherapy.Aim: To review obesity epidemiology and evaluate once-weekly semaglutide 2.4 mg regarding mechanism, efficacy, safety, and synergy with lifestyle changes.Materials and Methods: Narrative review of publications (2018–2025) from PubMed, Google Scholar, and other databases on obesity, GLP-1 analogs, and lifestyle trials. STEP program data, meta-analyses, and guidelines were included.Results: Risk factors include genetics, aging, sedentary lifestyle, and poor diet. Semaglutide, a GLP-1 receptor agonist, enhances insulin secretion, delays gastric emptying, and reduces appetite  (Papakonstantinou et al., 2024). In STEP Phase 3 trials, semaglutide 2.4 mg weekly produced ~15% mean weight loss over 68 weeks, versus ~2–5% with placebo  (Wilding et al., 2021) (Davies et al., 2021). About 69–79% achieved ≥10% loss, over half ≥15%  (Davies et al., 2021). Safety was consistent with GLP-1 class, dominated by mild-to-moderate gastrointestinal events  (Davies et al., 2021). Lifestyle modification alone yields 5–10% reduction, but in STEP 3, semaglutide plus intensive behavioral therapy achieved 16.0% versus 5.7% with lifestyle alone  (Wadden et al., 2021). Continued lifestyle support is crucial to maintain outcomes and limit post-withdrawal regain.Conclusions: Semaglutide represents a breakthrough in obesity pharmacotherapy, approaching bariatric surgery efficacy in some patients. Optimal outcomes occur with integration of diet, activity, and education. Future dual/triple agonists may enhance efficacy, but issues of cost, access, and adherence persist. Broad, equitable availability is essential for public health.